Mancozeb: growing risk for agricultural communities? - Atreya, Kishor; Sitaula, Bishal Kumar (Himalayan Journal of Sciences, 2011)
In a country where farmers rely on conventional wisdom to make decisions on farming practices and the government lacks clear policies based on solid research, pesticide overuse is emerging as a problem. Mancozeb, the widely applied pesticide in Nepal’s vegetable farming, has both short- and long-term health consequences to people exposed to its unsafe levels. A handful of studies in the hill regions of Nepal suggest that the pesticide is being sprayed to farms at much higher level than recommended. The widespread misuse and dangerous consequences of this pesticide suggest a need for more thorough study, better instruction, and more effective control. DOI: http://dx.doi.org/10.3126/hjs.v6i8.1794 Himalayan Journal of Sciences Vol.6 Issue 8 2010 pp.9-10